The Influence of Ownership Structure and Specific Characteristics To Capital Structure in Public Banks in Indonesia - Imas Maesaroh; Angga Sucitra H; Radis Diding R (AFEBI Economic and Finance Review, 2016)
This study aims to determine the effect of ownership structure and the specific characteristics of the capital structure in banks Indonesia. The results showed that partial ownership structure and the specific characteristics of the bank (profitability, size, and credit risk) had no significant effect on the capital structure, while the bank characteristics (expenses management) partially significant effect on the capital structure.JEL Classification: E50, G10, G21Keyword: capital structure, ownership structure, specific characteristics of bank